A method for preparing graphite phase carbon nitride composite nano-silicon negative electrode material

By constructing graphite phase carbon nitride composite nanosilicon structure in the negative electrode material of lithium-ion battery, using in-situ polymerization of CNTs and g-C3N4, the agglomeration and interface reaction problems of silicon nanostructured materials are solved, and the cycling performance of the battery is significantly improved and service life.

CN118005006BActive Publication Date: 2025-02-25GUANGDONG WENTAI NEW ENERGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410061564.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-16
Publication Date
2025-02-25
Estimated Expiration
2044-01-16

AI Technical Summary

Technical Problem

Silicon nano-anode materials have agglomeration effect and interface reactions caused by high specific surface area in lithium-ion batteries, resulting in a decrease in cycling performance and service life.

Method used

By mixing carbon nanotubes and modified silicon powder with cyanoic acid and melamine, thermal polymerization is carried out to form graphite phase carbon nitride composite nanosilicon anode material, and CNTs and g-C3N4 connected with C-N bonds are polymerized in situ on Si On the surface, a g-C3N4-CNTs/Si composite structure was constructed.

Benefits of technology

The circulation performance, service life and conductivity of the negative electrode material are improved. By building a large delocalized π-conjugated system, electron transfer and conductivity are enhanced, Si expansion is suppressed, and the circulation life of the material is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004666703080000111
    Figure BDA0004666703080000111
Patent Text Reader

Abstract

The present invention relates to a method for preparing a graphite phase carbon nitride composite nano silicon negative electrode material, and belongs to the technical field of lithium ion batteries. The present invention discloses a method for preparing a graphite phase carbon nitride composite nano silicon negative electrode material, which includes the following steps: A1: carbon nanotubes are placed in a mixed acid for infiltration treatment, and after solid-liquid separation, the solid is washed with deionized water to adjust the pH value to neutral, and then dried to obtain oxidized carbon nanotubes; A2: oxidized carbon nanotubes and modified silicon powder are added to a cyanuric acid solution, stirred and mixed to form a mixed solution, the mixed solution is poured into a melamine solution, stirred and placed to precipitate, and the filtered precipitate is washed with deionized water and dried to form a solid precipitate; A3: the solid precipitate is moved to a tubular furnace, argon gas is introduced, the temperature is increased and kept warm, and then cooled to obtain a graphite phase carbon nitride composite nano silicon negative electrode material. The cycle performance, service life and conductive performance of the silicon negative electrode material are improved by the above method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to a method for preparing a graphite phase carbon nitride composite nano-silicon negative electrode material. Background Art

[0002] Silicon is the most promising negative electrode material for lithium-ion batteries. It can react with lithium at room temperature to generate metal compounds with different lithium contents. Its theoretical specific capacity is as high as 4200mAhg -1 , the theoretical specific capacity of traditional graphite negative electrode materials is only one tenth of that. At the same time, silicon has a deintercalation potential of only 0.4V and is green, environmentally friendly and abundant in reserves. Therefore, silicon has become a research hotspot for negative electrode materials for lithium-ion batteries. However, there are still some problems with silicon negative electrode materials. The main problem is that silicon has a significant volume change during the process of lithium intercalation and deintercalation, which can easily cause the negative electrode material to crack and pulverize, thereby reducing battery performance. Silicon nano-sizing can effectively alleviate the volume expansion of silicon during lithium intercalation and deintercalation, but the following problems still exist: (1) Silicon nanoparticles will have a serious aggregation effect, resulting in poor cycle performance; (2) The high specific surface area of ​​nano-silicon particles will trigger a large number of interfacial reactions, forming a solid electrolyte interface film that consumes a large amount of ions, resulting in extremely low first-cycle coulomb efficiency.

[0003] Graphitic carbon nitride (g-C3N4) is a layered carbon nitride polymer with a conjugated π structure. Due to the strong covalent bond between carbon and nitrogen, g-C3N4 has extremely high thermal stability and is therefore widely used in the research of buffer materials for negative electrode materials with large volume changes. g-C3N4 can be synthesized from cyanuric acid and melamine by thermal polymerization, but the simple mixing of g-C3N4 and nano-silicon cannot solve the problem of nano-silicon agglomeration.

[0004] However, the intrinsic conductivity of g-C3N4 is low, which limits the application of g-C3N4 / Si in electrochemistry. The active conductive carbon matrix of carbon nanotubes (CNTs) can provide good electrical connection with active materials, improve the electron transfer of particles, and make the composite material have excellent electrical conductivity. Therefore, CNTs doping is carried out on the composite material to significantly improve its electrical conductivity. But if g-C3N4 / Si and CNTs are just simply physically mixed, the mixture will have an obvious two-phase physical interface, and g-C3N4 / Si and CNTs two materials in the mixture are mutually gathered and agglomerated, and the high electrical conductivity of CNTs cannot be fully utilized. Therefore, in view of the above problems, the present invention provides a corresponding preparation method. Summary of the invention

[0005] The present invention relates to a method for preparing a graphite phase carbon nitride composite nano silicon negative electrode material, and belongs to the technical field of lithium ion batteries. The present invention discloses a method for preparing a graphite phase carbon nitride composite nano silicon negative electrode material, which includes the following steps: A1: carbon nanotubes are placed in a mixed acid for infiltration treatment, and after solid-liquid separation, the solid is washed with deionized water to adjust the pH value to neutral, and then dried to obtain oxidized carbon nanotubes; A2: oxidized carbon nanotubes and modified silicon powder are added to a cyanuric acid solution, stirred and mixed to form a mixed solution, the mixed solution is poured into a melamine solution, stirred and placed to precipitate, and the filtered precipitate is washed with deionized water and dried to form a solid precipitate; A3: the solid precipitate is moved to a tubular furnace, argon gas is introduced, the temperature is increased and kept warm, and then cooled to obtain a graphite phase carbon nitride composite nano silicon negative electrode material. The cycle performance, service life and conductive performance of the silicon negative electrode material are improved by the above method.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A method for preparing a graphite phase carbon nitride composite nano-silicon negative electrode material, the method for preparing a graphite phase carbon nitride composite nano-silicon negative electrode material comprising the following steps:

[0008] A1: The carbon nanotubes are immersed in a mixed acid for treatment, and after solid-liquid separation, the solid is washed with deionized water to adjust the pH value to neutral, and then dried to obtain oxidized carbon nanotubes;

[0009] A2: adding oxidized carbon nanotubes and modified silicon powder to a cyanuric acid solution, stirring and mixing to form a mixed solution, pouring the mixed solution into a melamine solution, stirring and then allowing to stand for precipitation, and washing the filtered precipitate with deionized water and drying to form a solid precipitate;

[0010] A3: The solid precipitate is moved to a tubular furnace, argon gas is introduced, the temperature is increased and maintained, and then cooled to obtain a graphite phase carbon nitride composite nano-silicon negative electrode material.

[0011] Furthermore, in step A1, the mixed acid is composed of sulfuric acid and nitric acid mixed in a volume ratio of 1:3, the concentrations of the sulfuric acid and nitric acid are 16.2-18.4 mol / L and 12.4-14.6 mol / L, respectively, and the solid-liquid ratio of the carbon nanotubes and the mixed acid is 1-1.2:100 g / mL.

[0012] Furthermore, in the step A1, the soaking time and temperature are 10-12 hours and 70-80° C. respectively, and the pH value is 7.

[0013] Furthermore, in step A2, the mass ratio of the oxidized carbon nanotubes, the modified silicon powder, the cyanuric acid solution and the melamine solution is 0.1:0.1:1:1, and the mass fractions of the cyanuric acid solution and the melamine solution are 40-50% and 30-40%, respectively.

[0014] Furthermore, the method for preparing the modified silicon powder in step A2 comprises the following steps:

[0015] B1: Put magnesium silicide into a tube furnace, heat it up and keep it warm, take it out after cooling down, add hydrochloric acid solution and stir, then wash it with deionized water, and vacuum dry it to obtain porous silicon;

[0016] B2: Add porous silicon into the oxidation mixture and mix and stir, then wash with deionized water, put into a vacuum drying oven and dry to obtain modified silicon powder.

[0017] Furthermore, in the step B1, the heating rate is 10°C / min, the insulation temperature and time are 800°C and 1h respectively, and the cooling refers to cooling to room temperature.

[0018] Furthermore, in step B1, the concentration of the hydrochloric acid solution is 0.5 mol / L, the solid-liquid ratio of the magnesium silicide to the hydrochloric acid solution is 1:200 g / mL, the stirring time is 1.5-2 h, and the drying time and temperature are 8 h and 80° C., respectively.

[0019] Furthermore, in step B2, the oxidizing mixed solution consists of concentrated sulfuric acid and hydrogen peroxide in a volume ratio of 1:1, the concentration of the concentrated sulfuric acid is 18.4 mol / L, the mass fraction of the hydrogen peroxide is 2.7%-3.3%, the solid-liquid ratio of the porous silicon and the oxidizing mixed solution is 0.5:40 g / mL, the mixing time is 10 min, and the drying time and temperature are 8 h and 80°C, respectively.

[0020] Furthermore, in the step A2, the stirring time and temperature are 10-12h and 60-70°C respectively, the precipitation time is 5-6h, the drying temperature is 70-80°C, the heating rate in the step A3 is 2°C / min, the heating refers to heating to 500-550°C, and the insulation time is 3-4h.

[0021] The graphite phase carbon nitride composite nano-silicon negative electrode material is obtained by the above-mentioned preparation method.

[0022] Beneficial effects of the present invention:

[0023] 1. Porous silicon is prepared using magnesium silicide as raw material, and its specific surface area is increased. Oxidation increases the active sites on the surface of porous silicon, thereby enhancing the polymerization reaction with melamine and cyanuric acid, and significantly improving the cycle performance and service life of the silicon negative electrode.

[0024] 2. Melamine and cyanuric acid are polymerized in situ on the silicon surface, and the g-C3N4 formed by thermal polymerization can evenly coat silicon nanoparticles. The two-dimensional g-C3N4 and the one-dimensional CNTs are directly connected by CN bonds, and grow on Si through CN bonds to construct a g-C3N4-CNTs / Si composite structure. Compared with the simple mixing of g-C3N4, Si and CNTs, CNTs and g-C3N4 connected by CN bonds are polymerized in situ on the Si surface, so that the g-C3N4-CNTs / Si composite material forms a large delocalized π-conjugated system, which can make it easier for electrons to transfer from CNTs to g-C3N4, reduce the barrier height, and thus improve the conductivity and electron density of the composite material g-C3N4-CNTs / Si. At the same time, through the in-situ polymerization method, g-C3N4 can be uniformly grown and coated on the surface of Si. This g-C3N4-CNTs shell structure connected by CN bonds can not only inhibit the expansion of Si during the charge and discharge process and improve the cycle life of the composite material g-C3N4-CNTs / Si, but also improve the conductivity of the material and improve the rate performance of the composite material g-C3N4-CNTs / Si. DETAILED DESCRIPTION

[0025] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with embodiments.

[0026] Example 1

[0027] A method for preparing a graphite phase carbon nitride composite nano-silicon negative electrode material, the method for preparing a graphite phase carbon nitride composite nano-silicon negative electrode material comprising the following steps:

[0028] A1: The carbon nanotubes are immersed in a mixed acid for treatment, and after solid-liquid separation, the solid is washed with deionized water to adjust the pH value to neutral, and then dried to obtain oxidized carbon nanotubes;

[0029] A2: adding oxidized carbon nanotubes and modified silicon powder to a cyanuric acid solution, stirring and mixing to form a mixed solution, pouring the mixed solution into a melamine solution, stirring and then allowing to stand for precipitation, and washing the filtered precipitate with deionized water and drying to form a solid precipitate;

[0030] A3: The solid precipitate is moved to a tubular furnace, argon gas is introduced, the temperature is increased and maintained, and then cooled to obtain a graphite phase carbon nitride composite nano-silicon negative electrode material.

[0031] In step A1, the mixed acid is composed of sulfuric acid and nitric acid in a volume ratio of 1:3, the concentrations of the sulfuric acid and nitric acid are 16.2 mol / L and 12.4 mol / L respectively, and the solid-liquid ratio of the carbon nanotubes to the mixed acid is 1:100 g / mL.

[0032] The soaking time and temperature in step A1 are 10 h and 70° C., respectively, and the pH value is 7.

[0033] In step A2, the mass ratio of the oxidized carbon nanotubes, the modified silicon powder, the cyanuric acid solution and the melamine solution is 0.1:0.1:1:1, and the mass fractions of the cyanuric acid solution and the melamine solution are 40% and 30% respectively.

[0034] The method for preparing the modified silicon powder in step A2 comprises the following steps:

[0035] B1: Put magnesium silicide into a tube furnace, heat it up and keep it warm, take it out after cooling down, add hydrochloric acid solution and stir, then wash it with deionized water, and vacuum dry it to obtain porous silicon;

[0036] B2: Add porous silicon into the oxidation mixture and mix and stir, then wash with deionized water, put into a vacuum drying oven and dry to obtain modified silicon powder.

[0037] The heating rate in step B1 is 10° C. / min, the insulation temperature and time are 800° C. and 1 h respectively, and the cooling refers to cooling to room temperature.

[0038] The concentration of the hydrochloric acid solution in step B1 is 0.5 mol / L, the solid-liquid ratio of the magnesium silicide to the hydrochloric acid solution is 1:200 g / mL, the stirring time is 1.5 h, and the drying time and temperature are 8 h and 80° C., respectively.

[0039] In step B2, the oxidation mixture consists of concentrated sulfuric acid and hydrogen peroxide in a volume ratio of 1:1, the concentration of the concentrated sulfuric acid is 18.4 mol / L, the mass fraction of the hydrogen peroxide is 2.7%, the solid-liquid ratio of the porous silicon and the oxidation mixture is 0.5:40 g / mL, the mixing time is 10 min, and the drying time and temperature are 8 h and 80° C., respectively.

[0040] The stirring time and temperature in step A2 are 10 h and 60° C. respectively, the precipitation time is 5 h, the drying temperature is 70° C., the heating rate in step A3 is 2° C. / min, the temperature is raised to 500° C., and the insulation time is 3 h.

[0041] The graphite phase carbon nitride composite nano-silicon negative electrode material is obtained by the above-mentioned preparation method.

[0042] Example 2

[0043] A method for preparing a graphite phase carbon nitride composite nano-silicon negative electrode material, the method for preparing a graphite phase carbon nitride composite nano-silicon negative electrode material comprising the following steps:

[0044] A1: The carbon nanotubes are immersed in a mixed acid for treatment, and after solid-liquid separation, the solid is washed with deionized water to adjust the pH value to neutral, and then dried to obtain oxidized carbon nanotubes;

[0045] A2: adding oxidized carbon nanotubes and modified silicon powder to a cyanuric acid solution, stirring and mixing to form a mixed solution, pouring the mixed solution into a melamine solution, stirring and then allowing to stand for precipitation, and washing the filtered precipitate with deionized water and drying to form a solid precipitate;

[0046] A3: The solid precipitate is moved to a tubular furnace, argon gas is introduced, the temperature is increased and maintained, and then cooled to obtain a graphite phase carbon nitride composite nano-silicon negative electrode material.

[0047] In step A1, the mixed acid is composed of sulfuric acid and nitric acid in a volume ratio of 1:3, the concentrations of the sulfuric acid and nitric acid are 17.2 mol / L and 13.4 mol / L respectively, and the solid-liquid ratio of the carbon nanotubes to the mixed acid is 1:100 g / mL.

[0048] The soaking time and temperature in step A1 are 11 h and 75° C., respectively, and the pH value is 7.

[0049] In step A2, the mass ratio of the oxidized carbon nanotubes, the modified silicon powder, the cyanuric acid solution and the melamine solution is 0.1:0.1:1:1, and the mass fractions of the cyanuric acid solution and the melamine solution are 40% and 30% respectively.

[0050] The method for preparing the modified silicon powder in step A2 comprises the following steps:

[0051] B1: Put magnesium silicide into a tube furnace, heat it up and keep it warm, take it out after cooling down, add hydrochloric acid solution and stir, then wash it with deionized water, and vacuum dry it to obtain porous silicon;

[0052] B2: Add porous silicon into the oxidation mixture and mix and stir, then wash with deionized water, put into a vacuum drying oven and dry to obtain modified silicon powder.

[0053] The heating rate in step B1 is 10° C. / min, the insulation temperature and time are 800° C. and 1 h respectively, and the cooling refers to cooling to room temperature.

[0054] The concentration of the hydrochloric acid solution in step B1 is 0.5 mol / L, the solid-liquid ratio of the magnesium silicide to the hydrochloric acid solution is 1:200 g / mL, the stirring time is 1.5 h, and the drying time and temperature are 8 h and 80° C., respectively.

[0055] In step B2, the oxidation mixture consists of concentrated sulfuric acid and hydrogen peroxide in a volume ratio of 1:1, the concentration of the concentrated sulfuric acid is 18.4 mol / L, the mass fraction of the hydrogen peroxide is 2.7%, the solid-liquid ratio of the porous silicon and the oxidation mixture is 0.5:40 g / mL, the mixing time is 10 min, and the drying time and temperature are 8 h and 80° C., respectively.

[0056] The stirring time and temperature in step A2 are 11 h and 65° C. respectively, the precipitation time is 5 h, the drying temperature is 75° C., the heating rate in step A3 is 2° C. / min, the temperature is raised to 500° C., and the insulation time is 3.5 h.

[0057] The graphite phase carbon nitride composite nano-silicon negative electrode material is obtained by the above-mentioned preparation method.

[0058] Example 3

[0059] A method for preparing a graphite phase carbon nitride composite nano-silicon negative electrode material, the method for preparing a graphite phase carbon nitride composite nano-silicon negative electrode material comprising the following steps:

[0060] A1: The carbon nanotubes are immersed in a mixed acid for treatment, and after solid-liquid separation, the solid is washed with deionized water to adjust the pH value to neutral, and then dried to obtain oxidized carbon nanotubes;

[0061] A2: adding oxidized carbon nanotubes and modified silicon powder to a cyanuric acid solution, stirring and mixing to form a mixed solution, pouring the mixed solution into a melamine solution, stirring and then allowing to stand for precipitation, and washing the filtered precipitate with deionized water and drying to form a solid precipitate;

[0062] A3: The solid precipitate is moved to a tubular furnace, argon gas is introduced, the temperature is increased and maintained, and then cooled to obtain a graphite phase carbon nitride composite nano-silicon negative electrode material.

[0063] In step A1, the mixed acid is composed of sulfuric acid and nitric acid in a volume ratio of 1:3, the concentrations of the sulfuric acid and nitric acid are 18.4 mol / L and 14.6 mol / L respectively, and the solid-liquid ratio of the carbon nanotubes to the mixed acid is 1.2:100 g / mL.

[0064] The soaking time and temperature in step A1 are 12 hours and 80° C., respectively, and the pH value is 7.

[0065] In step A2, the mass ratio of the oxidized carbon nanotubes, the modified silicon powder, the cyanuric acid solution and the melamine solution is 0.1:0.1:1:1, and the mass fractions of the cyanuric acid solution and the melamine solution are 50% and 40%, respectively.

[0066] The method for preparing the modified silicon powder in step A2 comprises the following steps:

[0067] B1: Put magnesium silicide into a tube furnace, heat it up and keep it warm, take it out after cooling down, add hydrochloric acid solution and stir, then wash it with deionized water, and vacuum dry it to obtain porous silicon;

[0068] B2: Add porous silicon into the oxidation mixture and mix and stir, then wash with deionized water, put into a vacuum drying oven and dry to obtain modified silicon powder.

[0069] The heating rate in step B1 is 10° C. / min, the insulation temperature and time are 800° C. and 1 h respectively, and the cooling refers to cooling to room temperature.

[0070] The concentration of the hydrochloric acid solution in step B1 is 0.5 mol / L, the solid-liquid ratio of the magnesium silicide to the hydrochloric acid solution is 1:200 g / mL, the stirring time is 2 h, and the drying time and temperature are 8 h and 80° C., respectively.

[0071] In step B2, the oxidation mixture consists of concentrated sulfuric acid and hydrogen peroxide in a volume ratio of 1:1, the concentration of the concentrated sulfuric acid is 18.4 mol / L, the mass fraction of the hydrogen peroxide is 3.3%, the solid-liquid ratio of the porous silicon and the oxidation mixture is 0.5:40 g / mL, the mixing time is 10 min, and the drying time and temperature are 8 h and 80° C., respectively.

[0072] The stirring time and temperature in step A2 are 12 h and 70° C. respectively, the precipitation time is 6 h, the drying temperature is 80° C., the heating rate in step A3 is 2° C. / min, the temperature is raised to 550° C., and the insulation time is 4 h.

[0073] The graphite phase carbon nitride composite nano-silicon negative electrode material is obtained by the above-mentioned preparation method.

[0074] Comparative Example 1

[0075] On the basis of Example 2, the modified silicon powder in the preparation process of the graphite phase carbon nitride composite nano-silicon negative electrode material was removed and replaced with silicon powder of equal mass. Other conditions were consistent with Example 2.

[0076] The silicon powder model is silicon ash-M-56 / Shijiazhuang Leitai Technology Co., Ltd.

[0077] Comparative Example 2

[0078] On the basis of Example 2, a method for preparing a graphite phase carbon nitride composite nano-silicon negative electrode material is provided, wherein the method for preparing a graphite phase carbon nitride composite nano-silicon negative electrode material comprises the following steps:

[0079] A1: The carbon nanotubes are immersed in a mixed acid for treatment, and after solid-liquid separation, the solid is washed with deionized water to adjust the pH value to neutral, and then dried to obtain oxidized carbon nanotubes;

[0080] A2: Preparation of g-C3N4: Mix cyanuric acid solution and melamine solution in a mass ratio of 1:1, then heat and keep warm, cool to room temperature, and grind to obtain a g-C3N4 precursor;

[0081] A3: The g-C3N4 precursor, modified silicon powder and ethanol are stirred and mixed, ultrasonically treated, and then the oxidized carbon nanotubes are added and mixed, dried, heated and kept warm, and cooled to obtain a graphite phase carbon nitride composite nano-silicon negative electrode material.

[0082] In step A1, the mixed acid is composed of sulfuric acid and nitric acid in a volume ratio of 1:3, the concentrations of the sulfuric acid and nitric acid are 17.2 mol / L and 13.4 mol / L respectively, and the solid-liquid ratio of the carbon nanotubes to the mixed acid is 1:100 g / mL.

[0083] The soaking time and temperature in step A1 are 11 h and 75° C., respectively, and the pH value is 7.

[0084] The mass fractions of the cyanuric acid solution and the melamine solution in step A2 are 40% and 30% respectively, the heating temperature is 500° C., and the insulation time is 3 hours.

[0085] The method for preparing the modified silicon powder in step A3 comprises the following steps:

[0086] B1: Put magnesium silicide into a tube furnace, heat it up and keep it warm, take it out after cooling down, add hydrochloric acid solution and stir, then wash it with deionized water, and vacuum dry it to obtain porous silicon;

[0087] B2: Add porous silicon into the oxidation mixture, mix and stir, then wash with deionized water, put into a vacuum drying oven and dry to obtain modified silicon powder.

[0088] The heating rate in step B1 is 10° C. / min, the insulation temperature and time are 800° C. and 1 h respectively, and the cooling refers to cooling to room temperature.

[0089] The concentration of the hydrochloric acid solution in step B1 is 0.5 mol / L, the solid-liquid ratio of the magnesium silicide to the hydrochloric acid solution is 1:200 g / mL, the stirring time is 1.5 h, and the drying time and temperature are 8 h and 80° C., respectively.

[0090] In step B2, the oxidizing mixed solution consists of concentrated sulfuric acid and hydrogen peroxide in a volume ratio of 1:1, the concentration of the concentrated sulfuric acid is 18.4 mol / L, the mass fraction of the hydrogen peroxide is 2.7%, the solid-liquid ratio of the porous silicon and the oxidizing mixed solution is 0.5:40 g / mL, the mixing time is 10 min, and the drying time and temperature are 8 h and 80° C., respectively.

[0091] In the step A3, the mass ratio of g-C3N4 precursor, modified silicon powder, ethanol and oxidized carbon nanotubes is 2:0.1:3:0.1, the drying temperature is 70°C, the heating rate is 2°C / min, the temperature is raised to 500°C, and the insulation time is 3.5h.

[0092] The graphite phase carbon nitride composite nano-silicon negative electrode material is obtained by the above-mentioned preparation method.

[0093] 1. Performance Testing

[0094] Surface morphology: The graphite phase carbon nitride composite nano-silicon negative electrode materials prepared in Examples 1-3 and Comparative Examples 1-2 were used as samples, and the surface morphology and microstructure of the samples were analyzed using a scanning electron microscope.

[0095] Cycle performance test: The graphite phase carbon nitride composite nano-silicon negative electrode materials prepared in Examples 1-3 and Comparative Examples 1-2 were used as samples. The samples were made into half-cells of electrode materials, and the cycle performance of the samples was tested using the instrument: Xinwei CT-4008, specifically recording the charging capacity of the half-cell after one cycle and after 400 cycles, and calculating the cycle capacity retention rate. The calculation formula is: Cycle capacity retention rate % = b / a × 100%, a: charging capacity after one cycle, b: charging capacity after 400 cycles. The above test results are shown in Table 1.

[0096] Table 1 Test results

[0097]

[0098] From Table 1, it can be concluded that there is no agglomeration phenomenon in Examples 1-3 and Comparative Example 1, but there is a slight shedding phenomenon on the silicon surface in Comparative Example 1. The cycle capacity retention rate of Examples 1-3 is much greater than that of Comparative Example 1-2. The silicon powder used in Comparative Example 1 is not modified, and the silicon surface active sites are smaller than those in Examples 1-3, so the stability is poor. In the preparation process of Comparative Example 2, g-C3N4 is first synthesized and then mixed with silicon powder, so agglomeration occurs and the stability is poor.

[0099] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a graphite phase carbon nitride composite nano-silicon negative electrode material, characterized in that: The preparation method of the graphite phase carbon nitride composite nano-silicon negative electrode material comprises the following steps: A1: The carbon nanotubes are immersed in a mixed acid for treatment, and after solid-liquid separation, the solid is washed with deionized water to adjust the pH value to neutral, and then dried to obtain oxidized carbon nanotubes; A2: adding oxidized carbon nanotubes and modified silicon powder to a cyanuric acid solution, stirring and mixing to form a mixed solution, pouring the mixed solution into a melamine solution, stirring and then allowing to stand for precipitation, and washing the filtered precipitate with deionized water and drying to form a solid precipitate; A3: The solid precipitate is moved to a tube furnace, argon gas is introduced, the temperature is increased and kept warm, and then cooled to obtain a graphite phase carbon nitride composite nano-silicon negative electrode material; In step A2, the mass ratio of the oxidized carbon nanotubes, the modified silicon powder, the cyanuric acid solution and the melamine solution is 0.1:0.1:1:1, and the mass fractions of the cyanuric acid solution and the melamine solution are 40-50% and 30-40%, respectively; The method for preparing the modified silicon powder in step A2 comprises the following steps: B1: Put magnesium silicide into a tube furnace, heat it up and keep it warm, take it out after cooling down, add hydrochloric acid solution and stir, then wash it with deionized water, and vacuum dry it to obtain porous silicon; B2: adding porous silicon to the oxidation mixture, mixing and stirring, then washing with deionized water, and drying in a vacuum drying oven to obtain modified silicon powder; In step A1, the mixed acid is composed of sulfuric acid and nitric acid in a volume ratio of 1:3, the concentrations of the sulfuric acid and nitric acid are 16.2-18.4 mol / L and 12.4-14.6 mol / L, respectively, and the solid-liquid ratio of the carbon nanotubes to the mixed acid is 1-1.2:500 g / mL; In step B2, the oxidation mixture consists of concentrated sulfuric acid and hydrogen peroxide in a volume ratio of 1:1, the concentration of the concentrated sulfuric acid is 18.4 mol / L, the mass fraction of the hydrogen peroxide is 2.7%-3.3%, the solid-liquid ratio of the porous silicon and the oxidation mixture is 0.5:40 g / mL, the mixing time is 10 min, and the drying time and temperature are 8 h and 80° C., respectively.

2. The method for preparing a graphite phase carbon nitride composite nano-silicon negative electrode material according to claim 1, characterized in that: The soaking time and temperature in step A1 are 10-12 hours and 70-80° C., respectively, and the pH value is 7.

3. The method for preparing a graphite phase carbon nitride composite nano-silicon negative electrode material according to claim 1, characterized in that: The heating rate in step B1 is 10° C. / min, the insulation temperature and time are 800° C. and 1 h respectively, and the cooling refers to cooling to room temperature.

4. The method for preparing a graphite phase carbon nitride composite nano-silicon negative electrode material according to claim 1, characterized in that: The concentration of the hydrochloric acid solution in step B1 is 0.5 mol / L, the solid-liquid ratio of the magnesium silicide to the hydrochloric acid solution is 1:200 g / mL, the stirring time is 1.5-2 h, and the drying time and temperature are 8 h and 80° C., respectively.

5. The method for preparing a graphite phase carbon nitride composite nano-silicon negative electrode material according to claim 1, characterized in that: The stirring time and temperature in step A2 are 10-12h and 60-70°C respectively, the precipitation time is 5-6h, the drying temperature is 70-80°C, the heating rate in step A3 is 2°C / min, the heating refers to heating to 500-550°C, and the insulation time is 3-4h.

6. A graphite phase carbon nitride composite nano-silicon negative electrode material obtained by the preparation method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • G-C3N4 layer coated silicon negative electrode material, preparation method and application thereof

    CN116177502A

  • Silicon-carbon composite material for negative electrode material of lithium battery and preparation method of silicon-carbon composite material

    CN116885144A